Genome-Wide Analysis Identifies Germ-Line Risk Factors Associated with Canine Mammary Tumours. - Malin Melin; Patricio Rivera; Maja Arendt; Ingegerd Elvers; Eva Murén; Ulla Gustafson; Mike Starkey; Kaja Sverdrup Borge; Frode Lingaas; Jens Häggström; Sara Saellström; Henrik Rönnberg; et al. (PLoS Genetics, 2016)
Canine mammary tumours (CMT) are the most common neoplasia in unspayed female dogs. CMTs are suitable naturally occurring models for human breast cancer and share many characteristics, indicating that the genetic causes could also be shared. We have performed a genome-wide association study (GWAS) in English Springer Spaniel dogs and identified a genome-wide significant locus on chromosome 11 (praw = 5.6x10-7, pperm = 0.019). The most associated haplotype spans a 446 kb region overlapping the CDK5RAP2 gene. The CDK5RAP2 protein has a function in cell cycle regulation and could potentially have an impact on response to chemotherapy treatment. Two additional loci, both on chromosome 27, were nominally associated (praw = 1.97x10-5 and praw = 8.30x10-6). The three loci explain 28.1±10.0% of the phenotypic variation seen in the cohort, whereas the top ten associated regions account for 38.2±10.8% of the risk. Furthermore, the ten GWAS loci and regions with reduced genetic variability are significantly enriched for snoRNAs and tumour-associated antigen genes, suggesting a role for these genes in CMT development. We have identified several candidate genes associated with canine mammary tumours, including CDK5RAP2. Our findings enable further comparative studies to investigate the genes and pathways in human breast cancer patients.